Cost-Consequence Analysis of Mobile Stroke Units vs. Standard Prehospital Care and Transport - Reimer, Andrew P.; Zafar, Atif; Hustey, Fredric M.; Kralovic, Damon; Russman, Andrew N.; Uchino, Ken; Hussain, Muhammad S.; Udeh, Belinda L. (Frontiers in Neurology, 2020)
Background: Mobile stroke units (MSU) are the latest approach to improving time-sensitive stroke care delivery. Currently, there are no published studies looking at the expanded value of the MSU to diagnose and transport patients to the closest most appropriate facility. The purpose of this paper is to perform a cost consequence analysis of standard transport (ST) versus MSU. Methods and Results: A cost consequence analysis was undertaken within a decision framework to compare the incremental cost of care for patients with confirmed stroke that were served by the MSU versus their simulated care had they been served by standard emergency medical services between July 2014 and October 2015. At baseline values, the incremental cost between MSU and ST was $70,613 ($856,482 versus $785,869) for 355 patient transports. The MSU avoided 76 secondary interhospital transfers and 76 ED encounters. Sensitivity analysis identified 6 variables that had measurable impact of the model’s variability and a threshold value at which MSU becomes the optimal strategy: number of stroke patients (>391), probability of requiring transfer to a CSC (>0.52), annual cost of MSU operations (<$696,053), cost of air transfer (>$8,841), probability initial receiving hospital is a CSC (<0.32) and probability of ischemic stroke with standard transport (<0.76). Conclusions: MSUs can avert significant costs in the administration of stroke care once optimal thresholds are achieved. A comprehensive cost-effectiveness analysis is required to determine not just the operational value of an MSU, but also its clinical value to patients and society.